THE INFLUENCE OF MOTIVATIONS ON STUDENTS' ATTITUDES CONTINUING ACCOUNTING STUDIES IN SOUTH SUMATRA PROVINCE - Pratiwi, Arinta; Lukman, Hendro (Graduate Program of Universitas Tarumanagara, 2024)
The decline in student intention in choosing to study accounting in recent years shows a very massive decline both in the world and in Indonesia. The decline in choosing the accounting field can be seen both among those entering and enrolling in higher education. On the other hand, accounting personnel for the business world and government are always needed. The aim of the research is to empirically analyze the influence of income, social encouragement, and job opportunities on students' intention in continuing accounting studies. The research subjects were senior or vocational high school (SMA/K) students in South Sumatra Province with a sample size of 156 respondents. The sample collection method uses the convenience sampling method and the snowball sampling method. Distributing questionnaires digitally using Google Form. The research results show that income, social encouragement, and job opportunities have a positive and significant effect on students' intention in continuing their accounting studies. This research shows that the field of accounting for SMA/K students is a field that is still popular and has good prospects. The implication of this research is that SMA/K and higher education institutions must continue to provide insight to students regarding the future prospects of the accounting profession, and also always improve the curriculum to anticipate disruption to the accounting profession.